THE EDUCATIONAL PURPOSES IMPLIED IN THE OPERATIONAL GUIDELINES IN THE INCLUSIVE PERSPECTIVE: A LITERATURE REVIEW - Flávia Teodoro, Ana (Revista Gênero e Interdisciplinaridade, 2023)
The article presents the school educational purposes implicit in the Operational Guidelines from an inclusive perspective. The school in constant evolution, the social reality and the curricular transformations was studied from the perspective of different authors and publications. Constructivism and the attribution of management of the educational process to the State were also considered. In the dimension of pedagogical practice, authority, values and citizenship, the FEE are indicators as a philosophical and evaluative orientation. Social and educational public policies in the contemplation of diversity, inclusion and multiple cultural identities were addressed. The DC-GO contains the contents to be worked on in the school unit, considering the local reality. Therefore, the objective was to analyze the educational purposes from an inclusive perspective, contemplating the Operational Guidelines of the public education network. And, conceptualize the FEE implicit in the LDB/96; identify its characteristics in the context of DC-GO; list the provisions of inclusive pedagogy and the possibilities within the teaching-learning process. The systematic literature review methodology was based on scholars such as Libâneo, Lenoir, Tiballi, Freitas, Mantoan and Callas, among others. Findings: the multifactorial character of the problems marked by old paradigms, divergent concepts of the FEE function and the DC-GO propositions in the context of public policies. It was concluded that the FEE demand adaptations and cohesion in the formulation of educational policies. Integrating students with special needs requires reorganization of the school, attentive to the legislation. A critical teaching attitude is expected resulting from a collective effort aimed at the integral development of the student through reflective practices in the face of real needs.